Pengaruh Implementasi Kurikulum PAUD Berorientasi PISA terhadap Minat Belajar Anak Usia Dini - Suhayyatman Suhayyatman (AS-SABIQUN, 2026)
Indonesia’s low literacy and numeracy performance as reflected in the Programme for International Student Assessment (PISA) results requires strengthening education starting from early childhood education (Pendidikan Anak Usia Dini [PAUD]). This study aimed to analyze the implementation of a PISA-oriented PAUD curriculum in enhancing learning interest among young children. A descriptive qualitative approach was employed with teachers and learners at RA Darussalamah NWDI Praida Kroya Bagik Payung Timur, Suralaga Subdistrict, East Lombok Regency as the subjects. Data were collected through observations, in-depth interviews, and documentation over a three-month period, then analyzed through data reduction, data display, and conclusion drawing. The results indicate that the integration of literacy, numeracy, and contextual learning based on everyday life can increase children’s learning interest, as reflected in their enthusiasm, active participation, and curiosity during learning activities. This study concludes that a PISA-oriented PAUD curriculum has strategic implications for improving the quality of instruction and learning interest in early childhood and can serve as a reference for the development of PAUD curricula that are more adaptive to global demands.